Storytelling Strategies in Instagram Captions and Audience Emotional Engagement: A Narrative Analysis of @viralforjustice.co - Siti Mujanah; Kun Muhammad Adi (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study analyzes storytelling strategies in the Instagram content of the @viralforjustice.co account by examining the first 500 uploads published during the March to April 2026 period. Using a qualitative narrative analysis approach complemented by simple quantitative content analysis, the study identifies patterns in caption structures, emotional elements, and their relationship with audience engagement as measured by likes and comments. The findings reveal four dominant narrative models: problem–solution, victim–hero, call-to-action, and investigative disclosure. Captions employing urgency, victim–hero framing, and explicit calls to action consistently generate higher engagement than purely informative captions. These findings contribute to a better understanding of how digital civic movements can leverage storytelling strategies to encourage public participation and strengthen institutional accountability.